IMPLEMENTATION OF MAYOR'S REGULATION NUMBER 25 OF 2019 CONCERNING THE PONTIANAK SMART CITY MASTERPLAN 2019-2028 - Fronika Sindi Kledia; Pudjianto; Nurfitri Nugrahaningsih (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Public policy implementation is a crucial aspect in realizing the goals of effective and efficient governance. This study examines the implementation of Pontianak Mayor Regulation Number 25 of 2019 concerning the Pontianak Smart City Masterplan 2019–2028. The objective of this policy is to enhance technology-based city governance to improve public services and bureaucratic efficiency. This study uses Edward III's policy implementation theory, which emphasizes four main factors: communication, resources, disposition, and bureaucratic structure. The results show that the implementation of this policy still faces several challenges, such as a lack of inter-agency coordination, limited human and financial resources, and suboptimal technological infrastructure. One concrete example is the implementation of the Jendela Pontianak Integrasi(JEPIN) application, which still experiences obstacles in updating data and minimal public participation in its use. This study recommends increasing inter-agency synergy, more adequate budget allocation, and strengthening human resource capacity so that smart city policies can be implemented optimally.